PENILAIAN HARGA WAJAR SAHAM PT TELEKOMUNIKASI, Tbk - Dwiningsih Dwiningsih; Sri Hermuningsih (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2014)
The purpose of this study to determine the price of the stock is overvalued or undervalued condition if calculated by the method of the Dividend Discount Model (DDM) and the method of Price Earning Ratio (P / E Ratio) and examine the differences with both methods and compare the difference of the two methods to price stock market. The object of this research is the company Telecommunications Indonesia, Tbk. The data used in the form of secondary data that the financial statements and data company dividend distribution in cash. The research method using the Dividend Discount Model and Price Earning Ratio. The results showed that there were significant differences using the Price Earning Ratio is because stocks are undervalued condition, so as to determine the price of the stock is better to use the method of Price Earning Ratio. Keywords: Full Price/IntrinsicShares, Stock MarketPrices, Dividends, Earnings Per Share, DividendDiscount Model, Price Earning Ratio